Exclusion and embrace : a theological exploration of identity, otherness, and reconciliation - Volf, Miroslav (Nashville : Abingdon Press, 1996)
"Life at the end of the twentieth century presents us with a disturbing reality. Otherness, the simple fact of being different in some way, has come to be defined as in and of itself evil. Miroslav Volf contends that if the healing word of the gospel is to be heard today, Christian theology must find ways of speaking that address the hatred of the other. Reaching back to the New Testament metaphor of salvation as reconciliation, Volf proposes the idea of embrace as a theological response to the problem of exclusion. Increasingly we see that exclusion has become the primary sin, skewing our perceptions of reality and causing us to react out of fear and anger to all those who are not within our (ever-narrowing) circle. In light of this, Christians must learn that salvation comes, not only as we are reconciled to God, and not only as we "learn to live with one another," but as we take the dangerous and costly step of opening ourselves to the other, of enfolding him or her in the same embrace with which we have been enfolded by God."--BOOK JACKET
Introduction : The cross, the self, and the other -- Distance and belonging -- Exclusion -- Embrace -- Gender identity -- Oppression and justice -- Deception and truth -- Violence and peace
Includes bibliographical references (p. 307-327) and index
Keywords: Identification (Religion); Reconciliation -- Religious aspects -- Christianity